Analisis Pengaruh Country of Origin dan Foreign Branding Terhadap Persepsi Kualitas dan Sikap Konsumen pada Produk Kosmetika Pemutih - Sianturi, Elfride Irawati (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
It has been done a consumers’ behavior research with the aim to help marketer to predict consumer reaction to various kind of promotion and as a way ti understand consumer’s decision to buy. This research conducted experimentally using questionnaires as a primary data which were collected from participant. This research aimed to investigate how is the effect of country of origin and foreign branding towards perception and consumer’s attitude. This research has been done into three steps, i.e. preliminary test, manipulation check and main research. The results showed that country of origin affect perceptions and consumer attitudes. Consumer with a high level of country of origin has a higher perceptions and attitudes than a low country of origin Keywords : country of origin and foreign branding, quality perception, consumer behavior